Metabolomics integrated with network pharmacology and serum-urine pharmacochemistry unveils the antidiabetic mechanism of Anemarrhenae Rhizoma - Zhong, Xunlong; Peng, Huaidong; Xiao, Chang; Xiao, Chunhua; Zhu, Xinyu; Liang, Haixuan; Wang, Ruolun; Zhong, Yanmei; Feng, Jingwen (Frontiers in Endocrinology, 2025)
ObjectiveAnemarrhenae Rhizoma (AR) is a traditional Chinese medicine widely used for the treatment of type 2 diabetes mellitus (T2DM). However, the specific bioactive constituents responsible for its in vivo effects and their underlying mechanisms of action remain unclear. We hypothesise that serum-absorbed and metabolised AR components modulate key metabolic and inflammatory pathways in T2DM. To test this hypothesis, this study employs an integrated strategy combining metabolomics with serum-urine pharmacochemistry and network pharmacology to systematically identify AR’s active constituents and elucidate their multi-target mechanisms in T2DM management.MethodsUHPLC-Q-TOF-MS coupled with multivariate statistical analysis was employed to identify the AR-derived constituents in serum and urine of T2DM rats. Network pharmacology was utilised to predict the targets of the AR’s active components, while biochemical assays, liver histopathology, and metabolomics were performed to evaluate its therapeutic effects. Molecular docking and molecular dynamics (MD) simulations were conducted to assess the binding affinities between key components and their targets.Results77 AR components were identified, among which 47 prototypes and 11 metabolites were detected in serum and urine. The key bioactive constituents included sarsasapogenin, markogenin/neogitogenin, digitogenin, norathyriol, and mangiferin. AR treatment significantly reduced blood glucose and lipid levels, ameliorated insulin resistance, attenuated inflammation, and modulated the PPAR and NF-κB signalling pathways. Serum metabolomics analysis revealed 35 differential metabolites, with linoleic acid metabolism and PPAR signalling identified as the predominant metabolic pathways. Molecular docking and MD simulations demonstrated strong binding affinity between core components and key targets (PPARA, NFKB1, IL6, AKT1, IL1B). Pharmacological validation confirmed AR’s therapeutic efficacy in T2DM through regulation of these core targets.ConclusionAR ameliorates T2DM by suppressing NF-κB signalling and activating PPAR pathways, thereby improving metabolic dysregulation.